Utilization of Canva Application to Improve the Quality of Lecturers' Teaching Materials on the UPMI Campus - Siregar, Epi Supriyani; Tanjung, Ali Mukti; Siregar, Budi Alamsyah; Suma, Dewi; Rambe, Saima (Asian Journal of Community Services, 2025)
The purpose of this activity is to provide training to lecturers at UPMI University so that they can improve their digital competence in creating visually-based teaching materials using Canva . This activity also aims to foster lecturers' creativity in developing more engaging and easily understood teaching materials, as well as to enhance student involvement in the learning process. The research method employed in this activity is a training method that includes the introduction of basic theory, hands-on practice, and mentoring for lecturers in using the Canva application. The training is conducted step-by-step, allowing lecturers to create their own teaching materials, which are then evaluated by facilitators for feedback and design improvements. The results of this activity indicate that most of the lecturers who participated in the training successfully enhanced their competence in using Canva for creating teaching materials.